2014
DOI: 10.1038/leu.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptors against CD33/CD123 antigens efficiently target primary acute myeloid leukemia cells in vivo

Abstract: As significant numbers of acute myeloid leukemia (AML) patients are still refractory to conventional therapies or experience relapse, immunotherapy using T cells expressing chimeric antigen receptors (CARs) might represent a valid treatment option. AML cells frequently overexpress the myeloid antigens CD33 and CD123, for which specific CARs can be generated. However, CD33 is also expressed on normal hematopoietic stem/progenitor cells (HSPCs), and its targeting could potentially impair normal hematopoiesis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
166
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(176 citation statements)
references
References 33 publications
5
166
0
Order By: Relevance
“…Furthermore, consistent with Taussig et al (13), the present study identified the presence of CD33 on CD34 + CD38 -and CD34 + CD38 -Lin -cells in control samples. CD33-directed therapy has demonstrated efficacy in vivo against normal hematopoietic progenitor cells (23,24). The results of the present study have provided further evidence to support the hypothesis of Taussig et al (13), that utilizing CD33 antigen-targeted therapies may lead to potential HSC killing.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, consistent with Taussig et al (13), the present study identified the presence of CD33 on CD34 + CD38 -and CD34 + CD38 -Lin -cells in control samples. CD33-directed therapy has demonstrated efficacy in vivo against normal hematopoietic progenitor cells (23,24). The results of the present study have provided further evidence to support the hypothesis of Taussig et al (13), that utilizing CD33 antigen-targeted therapies may lead to potential HSC killing.…”
Section: Discussionsupporting
confidence: 82%
“…Recombinant technology is used to link the variable heavy and light domains of two antibodies as a single 55 kDa polypeptide chain. In clinical (12); (II) chimeric antigen receptor T cell using anti CD123 to target myeloid cells (13,14) (not yet in clinical trial); (III) single polypeptide chain bispecific engager antibodies (BiTE) recognizing CD3 and CD3 (15) or CD123 (16); (IV) double polypeptide chain dual affinity retargeting antibodies (DART) recognizing CD3 and CD123 (17,18). AML, acute myelogenous leukemia; VL, light chain; VH, heavy chain; CD3z, zeta chain of CD3; Co-stim, costimulatory molecules.…”
Section: Antibody Designmentioning
confidence: 99%
“…Thus among the strategies under development, DARTs may have superior qualities over BiTEs. When compared with chimeric T cell constructs (CARs) DARTs have the advantage that the requirement for in vitro T cell gene transduction is avoided (13,14). To optimize the physical properties of the chimeric antibody for AML treatment the antibody design ensures that the CD123/DART is more avid for the leukemic cell than the T cell, ensuring that T cells are preferentially bound by antibodies that have reached their target.…”
Section: Antibody Designmentioning
confidence: 99%
“…7 A fraction of normal HSCs may therefore survive therapies targeting CD123. 27 Finally, CD123 is also expressed on cells from other hematologic malignancies including Acute Lymphoblastic Leukemia (ALL), Chronic Myeloid Leukemia (CML), Myelo-Dysplastic Syndromes (MDS), Hodgkin Lymphoma (HL), Hairy Cell Leukemia (HCL) and others. 44,45 …”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that SPM-2 will be able to discriminate at least to a degree between AML-LSCs and remaining normal HSCs of a patient, due to its dual-targeting capacity and the greater combined surface density of CD33 and CD123 on AML-LSCs than on normal HSCs. 11,12,24,27,40,46 A preferential elimination of AML-LSCs over normal HSCs would be a distinct advantage, if it could be reached, because the surviving HSCs may be able to reconstitute the patient’s hematopoietic system after the end of therapy at least in part, possibly even without the need for a stem cell transplant. Here we have studied, whether SPM-2 in conjunction with activated human NK cells was capable of eliminating blasts from patients with a very broad range of AML subtypes, as predicted, 8 and found the prediction to be fulfilled.…”
Section: Introductionmentioning
confidence: 99%